2003
DOI: 10.1021/es026235n
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pesticide Residues on Museum Objects Repatriated to the Hupa Tribe of California

Abstract: In the past, it was common practice for museum professionals and private collectors to apply a variety of pesticide agents to objects in their collections to preserve them from depredations by microorganisms, fungi, and other pests. The Native American Graves Repatriation and Protection Act allows federally recognized tribes to request that museums return objects taken from their ancestors. Given that poor records were kept on the treatment of individual objects, it is unknown whether specific objects are cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…The DMN fraction of wash oil supplied by Huanghua Xinnuo Lixing Fine Chemical Co., Ltd., was analyzed by gas chromatography (GC) and its composition is reported in Tab. .…”
Section: Process and Methodsmentioning
confidence: 99%
“…The DMN fraction of wash oil supplied by Huanghua Xinnuo Lixing Fine Chemical Co., Ltd., was analyzed by gas chromatography (GC) and its composition is reported in Tab. .…”
Section: Process and Methodsmentioning
confidence: 99%
“…Water Environment Research, Volume 76, Number 6 1800 and sea water along a pollutant plume. Palmer et al (2003) revealed that pesticide residues on objects repatriated from a museum to a Native American tribe contained percent levels (wt/wt) of mercury on nearly every object and sub-percent levels of pdichlorobenzene, lindane and DDT on many objects.…”
Section: Monitoringmentioning
confidence: 99%
“…Determining organic pesticides on artifacts is more challenging due to wide variety of these species that have been used to treat these artifacts, the lower levels found on artifacts as they slowly volatilize or degrade over time, and the cost and complexity of the methods used to measure them. Gas Chromatography (GC) coupled with Mass Spectrometry (MS) is the method of choice here due to its ability to separate complex mixtures and provide definitive identification of specific pesticides at trace levels (Palmer et al 2003).…”
Section: Introductionmentioning
confidence: 99%